2014
DOI: 10.1136/archdischild-2014-306576.453
|View full text |Cite
|
Sign up to set email alerts
|

PPO.13 Does specialist antenatal care for women at risk of preterm birth affect patient selection, rate and outcomes of cervical cerclage?

Abstract: Background Evidence suggests that cervical cerclage should be offered to women after three or more previous preterm births (PTB) or second-trimester losses. Ultrasound-indicated cerclage reduces the rate of recurrent PTB in women with previous PTB or late miscarriage and a shortening cervix before 24 weeks. Patient selection is therefore critical for this intervention. Aim To assess the impact of a specialist antenatal service for women at risk of PTB on patient selection for cervical cerclage, cerclage rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…This allowed us to assess whether the largest and most comprehensive study on preterm birth clinics (Care 2019) [23] included all UK clinics described in other studies. All but four clinics in the Care 2019 study were identified and alternative studies including them were excluded from synthesis [25][26][27][28][29][30][31][32][33][34][35]. Of the four clinics reported anonymously in the Care 2019 study, three are also believed to have been reported elsewhere and so these studies were also excluded [24,36].…”
Section: Synthesis Of Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This allowed us to assess whether the largest and most comprehensive study on preterm birth clinics (Care 2019) [23] included all UK clinics described in other studies. All but four clinics in the Care 2019 study were identified and alternative studies including them were excluded from synthesis [25][26][27][28][29][30][31][32][33][34][35]. Of the four clinics reported anonymously in the Care 2019 study, three are also believed to have been reported elsewhere and so these studies were also excluded [24,36].…”
Section: Synthesis Of Resultsmentioning
confidence: 99%
“…Of the 20 included studies, 15 were full text articles [23, 24, 27-29, 33, 34, 49-56] and five were conference abstracts [26,[30][31][32]36]. Fourteen studies reported on an individual clinic [27-33, 36, 49-53, 56] and six studies reported on multiple clinics [23,24,26,34,54,55].…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“… 4. Burul et al [ 29 ], retrospective-cohort, clinic cases from January 2005 to December 2008, London-UK (abstract). 210 cerclage cases: 85 cases before the establish of the clinic and 125 afterwards Cervical cerclage 1.…”
Section: Resultsmentioning
confidence: 99%
“…The three most recent UK studies were published only as abstracts [ 28 – 30 ] and involved a retrospective case-note analysis of patients registered at the clinics. In Burul [ 29 ] the focus of the study was to collect data on cervical cerclage and pregnancy outcomes. A total 210 cerclage cases were identified at the PTB clinic, 85 cases before the PTB clinic was established (January 2005–December 2012) and 120 cases since January 2005–December 2012.…”
Section: Resultsmentioning
confidence: 99%